Web geometry optimisation of novel latticed LVL-webbed timber I-joists. (January 2023) - Harte, Annette M.; Baylor, Gordon; O'Ceallaigh, Conan
Abstract: This paper presents the finite element analysis of novel composite timber I-joists with curved latticed webs. The flanges of the joists were made from Norway Spruce whilst the curved latticed webs were made from laminated veneer lumber (LVL). The I-joists are analysed using the finite element method (FEM) with the component materials modelled as linear elastic orthotropic materials in both tension and compression. Good correlation was found between the experimental test results and the FE simulations when utilising material properties based on experimental investigation. The validated FE model was shown to reasonably predict the load-displacement behaviour and was used to assess the stress distributions within the novel I-joist and particularly in the latticed LVL web. The developed FE model provides a useful tool to further analyse and optimise the design. A geometric parameter study was carried out to enhance the structural performance of the novel I-joists by altering the geometry of the latticed web components and an optimised geometry is presented.